2016
DOI: 10.1080/19490976.2016.1188248
|View full text |Cite
|
Sign up to set email alerts
|

Rebooting the microbiome

Abstract: Using a murine Salmonella model of colitis, we recently reported that mice receiving a community of defined gut microbiota (MET-1) lost less weight, had reduced systemic inflammation and splenic S. typhimurium infection, and decreased neutrophil infiltration in the cecum, compared to vehicle controls. In addition, animals receiving MET-1 exhibited preserved tight junction protein expression (Zonula occludens-1, claudin-1), suggesting important effects on barrier function. In this addendum, we describe addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The genus of Bacteroides can produce propionate (Van den Abbeele et al, 2013; Walker and Parkhill, 2013) and are involved in the transformation of bile acids (Nicholson et al, 2012). The abundance of Bacteroides was high in IBD patients (Munoz et al, 2016). In the current study, abundance of Bacteroides was not restored to normal levels by HT121, while a increasing trend was observed in the other treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…The genus of Bacteroides can produce propionate (Van den Abbeele et al, 2013; Walker and Parkhill, 2013) and are involved in the transformation of bile acids (Nicholson et al, 2012). The abundance of Bacteroides was high in IBD patients (Munoz et al, 2016). In the current study, abundance of Bacteroides was not restored to normal levels by HT121, while a increasing trend was observed in the other treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to well-established defined communities, the probiotic cocktail VSL#3 and the fecal transplant substitute MET-1 have been tested on various human or animal intestinal cell lines (Caco-2, T84, and HT-29) (e.g., see references [138][139][140]. In most studies, however, the use of bacterial lysates or conditioned media was preferred over live bacteria (e.g., see references 72 and 141-144), because the (mainly anaerobic) gut bacteria cannot survive under the aerobic conditions needed for intestinal cell culture.…”
Section: Modeling the Host In Vitromentioning
confidence: 99%
“…Our study showed the presence and cellular localization of AvrA in precursor lesions using human clinical specimens [30] . Recent studies have indicated that Salmonella infection changes the composition of gut microbiota [31] , [32] , suggesting that other pathogenic bacteria and commensal bacteria may also regulate Wnt1 and its downstream signaling pathways. Interestingly, our data showed that tumors that developed due to AOM/DSS without Salmonella infection had no change in Wnt1 protein level; however, human CRC has deceased Wnt1.…”
Section: Discussionmentioning
confidence: 99%